RURAL CREDIT IN TEN RURAL COMMUNITIES IN THREE DISTRICTS OF THE REGION OF PUNO - Ada Luz Flores, O.; Luis A. Palao, Marco Vera Z., Ernesto Chura Y, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Puno region has two different zones in the native language, the northern zone is Quechua and the southern zone is Aymara. This research was carried out in the southern zone, in three districts and ten rural communities organized in an Association of Agricultural Producers and Fishermen of the Lake (APAPEL), where two credit institutions, CEDER and EDYFICAR through CARE PERU, have promoted rural credit in order to contribute to the improvement of the income of rural families. The objectives of the research are: a) identify the orientation of rural credit according to the type of activity, b) analyze the effect of rural credit on family income, and c) determine the delinquency rate of rural credit granted by two credit institutions. The method used is descriptive of evaluative type of inductive-deductive nature, under the microeconomic approach taking into account the CAUSE-EFFECT relationship. The population under study is made up of 453 peasant families associated with APAPEL, the sample size 164 borrowers representing 36% of the total, which was determined by the simple random sampling method. The observation techniques used were: the survey, documentary analysis, personal and group interviews structured with open and directed questions, finally direct observation to each user of rural credit and also to non-users. The results show that, of the 453 APAPEL associates and members of the credit institutions, only 164 families were borrowers, which means 36% of the demand for credit, for an average maximum amount of S/. 1,000.00 per family of free availability, interest rate 4.5% monthly at rebate and short term of 18 months with a grace period of 6 months. a). The investments according to the line of business were: 70% of the borrowers oriented their credit to cattle fattening and marketing, for an amount of S/. 99,500.00, which represents 68.2%; artisanal fishing of native fish species (Karachi, Ispi) and silverside with an amount of S/. 35,500.00, which represents 24.3%, in trout breeding 3%, with an amount of S/. 4,500.00; in pig and chicken breeding 1.4% for an amount of S/. 2,000.00, welding in general 2.4% for an amount of S/. 3,500.00 and transport 0.7% for an amount of S/. 1,000.00 respectively. b). The effect of the rural credit has been positive in the income level of the rural credit user families by an average of 27% depending on the activity and the capital rotation; in cattle fattening increased by 42.64%; cattle trade with an increase of 16.55%; sheep trade increased by 26.85%, in pig trade by 32.48% and finally in artisanal and commercial fishing by 18.03%, and c). The non-payment of the debt is because they were: subjects of rural credit without experience in the administration of the credit in 14%, inadequate credit orientation in 24%, loss in production in 7% due to adverse climatic factors; fall in prices of agricultural and livestock products in 38%, inopportune credit in 21% and finally by the scarce technical assistance in 3%.